Sasak Tribe Community Storytelling Model for Early Childhood Character Development - Baiq Rabiatul Adawiyah; Lalu Sumardi; Baedatul Izzah; Dayang Yuni Fadila; Leli Zarina Yani; Pruwita Sari (Lafadz Jaya Publisher, 2024)
This study aims to examine the application of the storytelling model in the Sasak community as an effort to develop the character of early childhood. Storytelling, as one of the local cultural traditions that has existed for a long time, has great potential in shaping character and instilling moral values in children. In the context of the Sasak community, folk tales and legends that are passed down orally contain important messages about kindness, honesty, courage, and responsibility. This study uses a quantitative survey approach with interview techniques and distributing questionnaires to parents, educators, and Sasak community leaders. The results of the study indicate that storytelling not only functions as a means of entertainment, but also as an effective method in children's character education, especially in introducing social and cultural values. In addition, children's active participation in listening to and discussing these stories strengthens their understanding of the norms that apply in society. This study concludes that the integration of the storytelling model in early childhood education can play an important role in children's character development, while maintaining the sustainability of local culture that is the identity of the Sasak community.